Online promotion dan shopping motivation: apakah berpengaruh terhadap compulsive buying? - Widiastuti Arini; Putri Tiara Jessica; Tiffany Yuanita; Peri A. Manaf (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
During the COVID-19 pandemic, all people in Indonesia must limit social interaction. In addition, this social restriction rule requires shopping centers to close, making consumers have to switch to making purchases online. This study aims to measure the most fit overall interaction relationship between the characteristics of shopping motivation and online promotion on compulsive buying. Primary data was obtained from a questionnaire that was filled out online by 246 respondents domiciled in Jabodetabek who met the requirements, namely buying clothes in April-July 2020. The data were analyzed using the F test and beta-beta coefficient test to determine the suitability and influence of each aspect. The test results show that hedonic shopping motivation has no suitability and is not influenced by online promotion of compulsive buying. The three dimensions of shopping motivation have compatibility and are directly influenced by online promotion, namely utilitarian motivation, peer influence, and social comparison. The three dimensions of motivation are influenced by online promotion, the dimensions of the discount size and time restriction. Based on this, the discount size and time restriction promotion methods are the most effective online promotion strategies to attract buyers.